Longitudinal Study Of BODE Index As Predictive Factor of COPD In Persahabatan Hospital Jakarta - Isep Supriyana; Faisal Yunus; Budhi Antariksa; Aria Kekalih (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2019)
Background: The BODE index is generally used for predicting mortality risk of COPD patients. The BODE index included the body mass index, degree of airflow obstruction (FEV1), dyspnea (MMRC questionnaire), and exercise capacity (6-minute walk test). Exacerbation of COPD associated with decreased health related quality of life (HRQoL). HRQoL has become an important outcome in respiratory patients as proved by St.George’s Respiratory Questionnaire (SGRQ). This study aim to find the correlation between BODE index with exacerbation and quality of life of COPD patients. We hypothesized that the higher BODE index score, the more frequent exacerbation occurrence and HRQoL decreased. Methods: Prospective cohort study of COPD patients was conducted in Persahabatan Hospital in November 2010 till June 2011. This study assessed the BODE index (at baseline) and followed at 3, 6, 9 and 12 months. Patient were also examined with SGRQ at baseline and followed at 6 and 12 months. We monitored the occurrence of exacerbation every month by telephone, observed their medical record, or visited the COPD’s clinic and emergency departement. Results: Eighty-five patients were examined at baseline with mean of BODE index 4.29 and SGRQ total score 41.42%. After one year follow up 52 patients have completed examination, 29 patients have not complete examination and 4 patients died. Using t-test analysis the correlation of BODE index between single and frequent exacerbation was significant (P